ACL Size, but Not Signal Intensity, Is Influenced by Sex, Body Size, and Knee Anatomy. Issue 12 (17th December 2021) - Barnett, Samuel C.; Murray, Martha M.; Flannery, Sean W.; Menghini, Danilo; Fleming, Braden C.; Kiapour, Ata M.; Proffen, Benedikt; Sant, Nicholas; Portilla, Gabriela; Sanborn, Ryan; Freiberger, Christina; et al.
Background: Little is known about sex-based differences in anterior cruciate ligament (ACL) tissue quality in vivo or the association of ACL size (ie, volume) and tissue quality (ie, normalized signal intensity on magnetic resonance imaging [MRI]) with knee anatomy. Hypothesis: We hypothesized that (1) women have smaller ACLs and greater ACL normalized signal intensity compared with men, and (2) ACL size and normalized signal intensity are associated with age, activity levels, body mass index (BMI), bicondylar width, intercondylar notch width, and posterior slope of the lateral tibial plateau. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Knee MRI scans of 108 unique ACL-intact knees (19.7 ± 5.5 years, 62 women) were used to quantify the ACL signal intensity (normalized to cortical bone), ligament volume, mean cross-sectional area, and length. Independent t tests were used to compare the MRI-based ACL parameters between sexes. Univariate and multivariate linear regression analyses were used to investigate the associations between normalized signal intensity and size with age, activity levels, BMI, bicondylar width, notch width, and posterior slope of the lateral tibial plateau. Results: Compared with men, women had significantly smaller mean ACL volume (men vs women: 2028 ± 472 vs 1591 ± 405 mm 3 ), cross-sectional area (49.4 ± 9.6 vs 41.5 ± 8.6 mm 2 ), and length (40.8 ± 2.8 vs 38.1 ± 3.1 mm) ( P < .001 for all), even after adjusting for BMI and bicondylar width. There was no difference in MRI signal intensity between men and women (1.15 ± 0.24 vs 1.12 ± 0.24, respectively; P = .555). BMI, bicondylar width, and intercondylar notch width were independently associated with a larger ACL ( R 2 > 0.16, P < .001). Younger age and steeper lateral tibial slope were independently associated with shorter ACL length ( R 2 > 0.03, P < .04). The combination of BMI and bicondylar width was predictive of ACL volume and mean cross-sectional area ( R 2 < 0.3). The combination of BMI, bicondylar width, and lateral tibial slope was predictive of ACL length ( R 2 = 0.39). Neither quantified patient characteristics nor anatomic variables were associated with signal intensity. Conclusion: Men had larger ACLs compared with women even after adjusting for BMI and knee size (bicondylar width). No sex difference was observed in signal intensity, suggesting no difference in tissue quality. The association of the intercondylar notch width and lateral tibial slope with ACL size suggests that the influence of these anatomic features on ACL injury risk may be partially explained by their effect on ACL size. Registration: NCT02292004 and NCT02664545 (ClinicalTrials.gov identifier).